2014
DOI: 10.1371/journal.pone.0091122
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fractures and Bone Mineral Density in the Elderly—Importance of Serum 25-Hydroxyvitamin D

Abstract: BackgroundThe significance of serum 25-hydroxyvitamin D [25(OH)D] concentrations for hip fracture risk of the elderly is still uncertain. Difficulties reaching both frail and healthy elderly people in randomized controlled trials or large cohort studies may in part explain discordant findings. We determined hazard ratios for hip fractures of elderly men and women related to serum 25(OH)D, including both the frail and the healthy segment of the elderly population.MethodsThe AGES-Reykjavik Study is a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 38 publications
2
40
0
4
Order By: Relevance
“…The data set chosen to estimate the relation of hip fractures to 25(OH)D concentration comes from Iceland. In that study, 5764 men and women aged 66–96 y were followed up for 5.4 y 69 . Using data for hip fracture rates given in Figure 1 of that study, increasing 25(OH)D concentration to above 100 nmol/L would reduce fracture rates by an estimated 22%.…”
Section: Methodsmentioning
confidence: 99%
“…The data set chosen to estimate the relation of hip fractures to 25(OH)D concentration comes from Iceland. In that study, 5764 men and women aged 66–96 y were followed up for 5.4 y 69 . Using data for hip fracture rates given in Figure 1 of that study, increasing 25(OH)D concentration to above 100 nmol/L would reduce fracture rates by an estimated 22%.…”
Section: Methodsmentioning
confidence: 99%
“…Steingrimsdottir et al . performed a prospective study of 5764 men and women, and showed that, compared with reference values (50–75 nmol/L), values <30 nmol/L were associated with significantly lower BMD of the femoral neck.…”
Section: Introductionmentioning
confidence: 99%
“…A body of published evidence consistently demonstrates associations of low serum 25-hydroxyvitamin D [25(OH)D] concentrations with lower bone mineral density (BMD) and fractures [15]. Results of these observational studies contrast to some extent with findings from meta-analyses of low-dose vitamin D supplementation trials, which demonstrate only modest or null effects on BMD and fracture prevention [68].…”
Section: Introductionmentioning
confidence: 99%